Cowboy Singer Planning Raton Holiday Return (Raton, NM Raton Range, 1997)
Article to promote a Christmas Concert by Cowboy singer Michael martin Murphey.
Newspaper article + Photograph of Michael Martin Murphey
Master list item #: 92
File location is in the Raton file Cabinet
Keywords: Murphey, Michael Martin -- Musician; Sweich, Frank -- Musician; Murphey, Ryan -- Musician; Coe, David -- Musician; Roller, Gary -- Musician; Woodbury, Don -- Musician; Featherston, Leroy -- Musician; Rio Grand Band -- Music Group; Live Performance; Performance Promotion; Christmas Carols; Music Performance; Cowboy Poetry; Western Songs; Shuler Theater; Raton, New Mexico